2016
DOI: 10.11607/jomi.4224
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Effect of Erbium-Doped Yttrium Aluminum Garnet Laser and Photodynamic Therapy on Aggregatibacter Actinomycetemcomitans Biofilm on Implant Surface

Abstract: Purpose: Peri-implantitis is a common complication of dental implants. The first step of treatment is elimination of bacterial biofilm and disinfection of the implant surface. This study sought to compare the effects of an erbium-doped yttrium aluminum garnet (Er:YAG) laser, photodynamic therapy using an indocyanin green-based photosensitizer (ICG-based PS) and diode laser, toluidine blue O (TBO) photosensitizer and light-emitting diode (LED) light source, and 2% chlorhexidine (CHX) on biofilm of Aggregatibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 33 publications
2
25
2
Order By: Relevance
“…When this technique is used to eradicate bacterial cells, it is termed antimicrobial photodynamic therapy [98]. Various light sources have been used in in vitro and in vivo studies, such as yttrium aluminum garnet (YAG) lasers [162, 163], potassium yttrium tungstate (KYW) lasers [164], and femtosecond [165] and near-infrared lasers [166], showing the potential of photodynamic therapy to treat and control biofilm-based infections. Multiple bacterial biofilms have been shown to be eradicated using diode lasers (405–940 nm) and different photosensitizers on acrylic resin, glass, titanium, and zirconia, which in some cases was shown to be synergistic with antibiotic treatment [163, 167, 168, 169, 170, 171, 172, 173, 174].…”
Section: Main Textmentioning
confidence: 99%
“…When this technique is used to eradicate bacterial cells, it is termed antimicrobial photodynamic therapy [98]. Various light sources have been used in in vitro and in vivo studies, such as yttrium aluminum garnet (YAG) lasers [162, 163], potassium yttrium tungstate (KYW) lasers [164], and femtosecond [165] and near-infrared lasers [166], showing the potential of photodynamic therapy to treat and control biofilm-based infections. Multiple bacterial biofilms have been shown to be eradicated using diode lasers (405–940 nm) and different photosensitizers on acrylic resin, glass, titanium, and zirconia, which in some cases was shown to be synergistic with antibiotic treatment [163, 167, 168, 169, 170, 171, 172, 173, 174].…”
Section: Main Textmentioning
confidence: 99%
“…Similarly, Saffarpour et al demonstrated that the 0.2% CHX group had the lowest colony count. (24) PDT applications have simple concepts but several factors complicate them. Further studies are required for determination of proper and exact parameters for each disease; this includes factors related to photosensitizers such as the transmission method and the duration of application and parameters related to the wavelength, irradiation exposure time, and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the tip was 8 mm with an energy density of 110 J/cm 2 . (24) The device was placed at a fixed distance of 1 mm, perpendicular to the surfaces of the discs for 2 minutes. The output power of the device was 220 mW, which was measured by a power meter (LaserPoint s.r.l., Mi-plied by 20 to calculate the numbers in each ml.…”
Section: Pdt Procedurementioning
confidence: 99%
See 2 more Smart Citations